Sports psychiatry and medical views on mild traumatic brain injury in competitive sport: A current review and recommendations - Gonzalez Hofmann, C.; Fontana, R.; Parker, T.; Deutschmann, M.; Dewey, M.; Reinsber, C.; Claussen, M. C.; Scherr, J.; Jeckell, A. S. (Deutsche Zeitschrift für Sportmedizin, 2021)
Head injuries are common in competitive and recreational sport. Nomenclature, though inconsistent, identifies mild traumatic brain injury (mTBI) based on acute diagnostic criteria, whereas a sport-related concussion (SRC) is event-related and specific to mTBI experienced while participating in athletic ac- tivity. The effects of SRC are often neurological, neuropsychological and/or psychiatric with a variety of symptoms.